Understanding the heat stress mitigation mechanisms during pollen development in Gossypium hirsutum L. - Rabia Habib; Zulqurnain Khan; Abdel-Halim Ghazy; Shoaib ur Rehman; Kotb A. Attia; Maria Siddique; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Abu Bakar Saddique; Ummara Waheed (Molecular Biology Reports, 2026)

Ratemaking under indexation: How policy clauses compound into retail electricity tariffs - Fahad Bin Abdullah; Muhammad Arsalan Aqeeq; Falak Shad Memon; Maria Abdullah; Sumaira Chamadia (Utilities Policy, 2026)

Preliminary survey of anthelmintic efficacy in selected smallholder sheep and goat flocks in Sarawak, Malaysia - Ali Saidu; Bura Thlama Paul; Maria Eva Barudi; Faez Firdaus Abdullah Jesse; Juriah Kamaludeen; Suhaili Mustafa; Masnindah Malahubban; Ali Hanafiah Hakim; Krishnan Nair Balakrishnan; Mohd Azmi Mohd Lila; Abubakar Abdullahi Biu (Tropical Animal Health and Production, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Influence of agricultural residues on the formation of TiO2 phases: Real-time in situ X-ray diffraction monitoring in a reaction chamber - Rodrigo P. Feitosa; Johar Amin Ahmed Abdullah; Ramón R. Peña-Garcia; Maria G. Fonseca; Edson C. Silva-Filho; Santiago Medina-Carrasco; Maria del Mar Orta Cuevas; Josy A. Osajima (Chemical Engineering Journal, 2026)

Eucalyptus wood waste biochar as an eco-friendly adsorbent for arsenic detoxification in wastewater - Yu Shuang Ren; Muhammad Ilyas; Islamud Din; Syeda Maria Ali; Shahid Iqbal; Thiago Machado da Silva Acioly; Zhanate Idrisheva; Khalid Z. Elwakeel; Alibek Ydyrys; Abdullah Faiz Al Asmari; Saiful Islam (Natural Product Research, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Photoperiod and temperature: Key abiotic drivers of horticultural crop physiology in a changing climate - Muhammad Atiq Ashraf; Shumaila Nawaz; Uzma Bilal; Maria Abubakar; Shumaila Anam; Muhammad Azam; Burhan Khalid; Abdullah; Muhammad Asim; Rabbya Rayan Shah; Muhammad Ateeq (Biologia, 2026)

Assessing hurricane risks in coastal communities: A participatory and probabilistic approach incorporating evolving hazard conditions - Abdullah M. Braik; Xuan Ma; Maria Koliou; James M. Kaihatu; Sherry Pinell (Engineering Structures, 2026)

Cervical and thoracolumbar transspinal stimulation at 0.3 Hz and 30 Hz facilitates neuronal excitability in healthy humans: a randomized cross-over study - Abdullah M. Sayed Ahmad; Maria Knikou (Experimental Brain Research, 2026)

Unraveling the therapeutic landscape of miRNAs in pancreatic cancer - Zeinab A. El-Moaty; Maria Wagdy Wasef; Yara A. Elsayed; Amina Sayed Shafiq; Mai A. Elnagar; Hadeer Rashad Mohamed; Ahmed E. Elesawyf; Sherif S. Abdel Mageedg; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Rabab S. Hamad; Raydaa Abdullah S. Alshomrani; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comparative Analysis of the Efficiencies of Two Low Cost Adsorbents for Carbon Dioxide Capture - Sayyaf Yousaf; Haris Abdullah Noor; Muhammad Wajid Ullah; Alireza Noorpoor; Adnan Ahmad Tahir; Maria Siddique; Romana Khan (International Journal of Environmental Research, 2025)

Modulation of Sodium and Ammonia Transporters in the Context of Viral Gill Diseases in Common Carp ( Cyprinus carpio ) - Maria Zawisza; Muhammad Abdullah; Magdalena Marcinkowska; Marek Matras; Krzysztof Rakus; Mikolaj Adamek (Journal of Fish Diseases, 2025)
Osmoregulation and ammonia removal are among key physiological processes that take place in gills and affect fish homeostasis and well‐being. These processes can be disrupted by numerous environmental factors, but also by viral infections, especially those leading to severe gill disorders. The mechanisms of how viruses disrupt osmoregulation and ammonia removal in fish have not been extensively studied. We propose further exploration of the molecular and functional basis of viral induced gill disorders by studying the gene expression and enzyme activity of Na + /K + ‐ATPases (NKA) and ammonia transporters in the gills and kidney of common carp during infection with two viruses: carp edema virus (CEV) and cyprinid herpesvirus 3 (CyHV‐3). In the case of NKA, the expression of subunit α of selected NKA was affected by both viruses; however, no discernible trends were observed in the gills and kidneys. The enzyme activity of NKA was significantly reduced in the gills during infection with both CEV and CyHV‐3. Moreover, our immunohistochemical studies showed that during infection with CEV and CyHV‐3, NKA‐rich cells are transferred from the primary lamellae to the more superficial space and to the secondary lamellae of the gills. In the case of ammonia transporters, both CEV and CyHV‐3 infection resulted in downregulation of the expression of major transporters gdh1 , Rhag , and Rhbg , allowing us to partly explain the ammonia accumulation in blood observed during infection with these viruses. This study highlighted that virus induced gill disorders may lead to disruption of osmoregulation and ammonia removal by dysregulating the expression and activity of NKA and ammonia transporters.

Distribution and nest occupancy patterns of Oecophylla smaragdina (hymenoptera: formicidae) colonies in Southeast Asian oil palm plantations - Moïse Pierre Exélis; Rosli Ramli; Azarae Hj Idris; Rabha W. Ibrahim; Gemma Maria Clemente-Orta; Camilo Ayra-Pardo; Muhamad Shirwan Abdullah Sani (Journal of Asia-Pacific Entomology, 2025)

Specificity protein 1 (SP1) plays an essential role in early bovine embryo development - Anup K. Talukder; Abdullah A. Naib; Solomon Mamo; Laura Thompson; Juliana G. Ferst; Maria B. Rabaglino; John A. Browne; Trudee Fair; Pat Lonergan (Theriogenology, 2025)

Consequences of human conflicts on aquatic ecosystems in drylands areas: Future management perspective - Luciana G. Barbosa; Ilia Ostrovsky; Manuela Morais; Elena Anufriieva; Gema Parra; Egor Zadereev; Antonio Camacho; Antje Schwalb; Simonetta Bagella; Rosemberg F. Menezes; Luz Marina Soto; Carlos López; et al. (Journal of Arid Environments, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

Distribution modelling and future prediction of a threatened species - Heracleum candicans Wall. ex DC.; Within the framework of biotic and abiotic interactions - Jawad Hussain; Shujaul Mulk Khan; Muhammad Shakeel Khan; Zafeer Saqib; Abdullah; Zeeshan Ahmad; Maria Shah; Nazir Mohammad; Zareena Batool; Amir Sohail; Jie Liu (Journal of Environmental Management, 2025)

Regionalized Life Cycle Assessment of Silicon Wafers Supply Chains in the Semiconductor Industry - Abdullah Ahsan Ahmed; René H. Reich; Andrea Di Maria; Lizzie Boakes; Cédric Rolin; Karel Van Acker (Circular Economy and Sustainability, 2025)

Post-tornado automated building damage evaluation and recovery prediction by integrating remote sensing, deep learning, and restoration models - Abdullah M. Braik; Maria Koliou (Sustainable Cities and Society, 2025)

Fusarium Keratitis: A Systematic Review (1969 to 2023) - Maria Eduarda Carvalho Cintra; Maryanna da Silva Dantas; Abdullah M. S. Al-Hatmi; Rafael Wesley Bastos; Luana Rossato (Mycopathologia, 2024)

A review of heavy metals pollution in riverine sediment from various Asian and European countries: Distribution, sources, and environmental risk - Maria Zeb; Kifayatullah Khan; Muhammad Younas; Abida Farooqi; Xianghui Cao; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Abdullah G. Al-Sehemi (Marine Pollution Bulletin, 2024)

Iron salicylaldehydate conjugated metal–organic framework for quasi solid-state supercapacitor - Abdul Khayum Mohammed; Ajmal Pandikassala; Pilar Pena Sánchez; Safa Abdullah Gaber; Stefano Canossa; Maria Kurian; Gigi Xavier; Yao He; Felipe Gándara; Sreekumar Kurungot; Dinesh Shetty (Chemical Engineering Journal, 2024)

Interactions between arm and leg neuronal circuits following paired cervical and lumbosacral transspinal stimulation in healthy humans - Abdullah M. Sayed Ahmad; Andreas Skiadopoulos; Maria Knikou (Experimental Brain Research, 2024)

Pythium and Globisporangium species associated with cucumber rhizosphere causing damping-off and their effects on cucumber seed decay in Oman - Issa Hashil Al-Mahmooli; Maria Renate Finckh; Rethinasamy Velazhahan; AlMohanad Mohammed AlJabri; Adnan Šišić; Shah Hussain; Raid Abdel-Jalil; Abdullah Mohammed Al-Sadi (Archives of Microbiology, 2024)

Ecotourism and mangrove conservation in Southeast Asia: Current trends and perspectives - Austin Blanton; Ewane Basil Ewane; Freddie McTavish; Michael S. Watt; Kerrylee Rogers; Redeat Daneil; Irene Vizcaino; Ana Novo Gomez; Pavithra S. Pitumpe Arachchige; Shalini A.L. King; G.A. Pabodha Galgamuwa; Martha Lucia Palacios Peñaranda; et al. (Journal of Environmental Management, 2024)

Central IRF4/5 Signaling Are Critical for Microglial Activation and Impact on Stroke Outcomes - Conelius Ngwa; Abdullah Al Mamun; Shaohua Qi; Romana Sharmeen; Maria P. Blasco Conesa; Bhanu P. Ganesh; Bharti Manwani; Fudong Liu (Translational Stroke Research, 2024)

No association between markers of systemic inflammation and endothelial dysfunction with Alzheimer’s disease progression: a longitudinal study - Arne van Setten; Jeroen F. Uleman; René J. F. Melis; Brian Lawlor; Niels P. Riksen; Jurgen A. H. R. Claassen; Rianne A. A. de Heus; Ricardo Segurado; Sean Kennelly; Marcel G. M. Olde Rikkert; Robert Howard; Florence Pasquier; et al. (GeroScience, 2024)
Introduction Systemic inflammation and endothelial dysfunction are potentially modifiable factors implicated in Alzheimer’s disease (AD), which offer potential therapeutic targets to slow disease progression. Methods We investigated the relationship between baseline circulating levels of inflammatory (TNF-α, IL-1ß) and endothelial cell markers (VCAM-1, ICAM-1, E-selectin) and 18-month cognitive decline (ADAS-cog12) in 266 mild-to-moderate AD patients from the NILVAD study. We employed individual growth models to examine associations, potential mediation, and interaction effects while adjusting for confounders. Results The average increase in ADAS-cog12 scores over all patients was 8.1 points in 18 months. No significant association was found between the markers and the rate of cognitive decline. Mediation analysis revealed no mediating role for endothelial cell markers, and interaction effects were not observed. Discussion Our results do not support the role of systemic inflammation or endothelial dysfunction in progression in persons with AD.

Enhancing electricity distribution efficiency in Pakistan: A framework for progress and action - Fahad Bin Abdullah; Muhammad Arsalan Aqeeq; Rizwan Iqbal; Maria Abdullah; Falak Shad Memon (Utilities Policy, 2024)

A comprehensive study on chemical and biological profiles of Algerian Azadirachta indica (A. Juss) - Ahmed Boukeloua; Soudani Leila; Hamdi Bendif; Ahmed M. Mustafa; Mehmet Boga; Maria Luísa Serralheiro; Mustafa Abdullah Yilmaz; Ismail Yener; Stefania Garzoli (Phytochemistry Letters, 2024)

Evaluation of sustainable manufacturing performance – A case illustration with multistakeholder perspective - Song Xu; Thulasi Mani Murugesan; Abdullah Abdullatif Aly Elfar; Maria Pon Reka Durairaj (Journal of Cleaner Production, 2024)

Soleus H-reflex amplitude modulation during walking remains physiological during transspinal stimulation in humans - Abdullah M. Sayed Ahmad; Meghan Raphael; Jessy Feng Han; Yoseph Ahmed; Mohamed Moustafa; Shammah K. Solomon; Andreas Skiadopoulos; Maria Knikou (Experimental Brain Research, 2024)

Preservation of plant‐wax biomarkers in deserts: implications for Quaternary environment and human evolutionary studies - Deepak Kumar Jha; Robert Patalano; Jana Ilgner; Hema Achyuthan; Abdullah M. Alsharekh; Simon Armitage; James Blinkhorn; Nicole Boivin; Paul S. Breeze; Ravindra Devra; Nicholas Drake; Huw S. Groucutt; et al. (Journal of Quaternary Science, 2024)
Analysis of plant‐wax biomarkers from sedimentary sequences can enable past environmental and hydrological reconstruction and provide insights into past hominin adaptations. However, biomarker preservation in desert contexts has been considered unlikely given the sparse nature of the vegetation within the landscape. Here we evaluate the preservation of n ‐alkanes and fatty acids collected from four depositional sequences associated with archaeological contexts in the Nefud Desert, Saudi Arabia, and the Thar Desert, India. Pleistocene and Holocene samples were selected to understand the effects of age on preservation. The results of molecular distribution patterns and indices, particularly the high carbon preference index and average chain length, show the preservation of plant‐wax biomarkers in both the Holocene and Pleistocene desert sequences, while δ 13 C values and organic content provide insights into the vegetation contributing to the plant‐wax organic pool. This study provides a baseline for understanding human–environment interactions and for reconstructing changes in arid land habitats of relevance to hominins during the Quaternary.

Seismic assessment of bridges through structural health monitoring: a state-of-the-art review - Christos Karakostas; Giuseppe Quaranta; Eleni Chatzi; Abdullah Can Zülfikar; Oğuzhan Çetindemir; Guido De Roeck; Michael Döhler; Maria Pina Limongelli; Geert Lombaert; Nurdan Memişoğlu Apaydın; Vikram Pakrashi; Costas Papadimitriou; et al. (Bulletin of Earthquake Engineering, 2024)
The present work offers a comprehensive overview of methods related to condition assessment of bridges through Structural Health Monitoring (SHM) procedures, with a particular interest on aspects of seismic assessment. Established techniques pertaining to different levels of the SHM hierarchy, reflecting increasing detail and complexity, are first outlined. A significant portion of this review work is then devoted to the overview of computational intelligence schemes across various aspects of bridge condition assessment, including sensor placement and health tracking. The paper concludes with illustrative examples of two long-span suspension bridges, in which several instrumentation aspects and assessments of seismic response issues are discussed.

Response to carvacrol monoterpene in the emergence of Allium cepa L. seeds exposed to salt stress - Larisse Bernardino dos Santos; Jailson Renato de Lima Silva; Amanda Maria Tavares Moreira; Jean Paul Kamdem; Momin Khan; Niaz Muhammad; Abdullah F. AlAsmari; Fawaz Alasmari; Antonia Eliene Duarte; Mohammad Ibrahim (Environmental Science and Pollution Research, 2024)

Comprehensive metabolite and biological profile of “Sulmona Red Garlic” ecotype’s aerial bulbils - Annalisa Chiavaroli; Fabrizio Masciulli; Cinzia Ingallina; Luisa Mannina; Maria Loreta Libero; Simonetta Cristina Di Simone; Alessandra Acquaviva; Nilofar; Lucia Recinella; Sheila Leone; Luigi Brunetti; Simone Carradori; et al. (Food Research International, 2024)

Hydrothermal carbonization of Typha australis: Influence of stirring rate - Omar M. Abdeldayem; Md Abdullah Al Noman; Capucine Dupont; David Ferras; Lat Grand Ndiaye; Maria Kennedy (Environmental Research, 2023)

Heavy metals in five commonly consumed fish species from River Swat, Pakistan, and their implications for human health using multiple risk assessment approaches - Kifayatullah Khan; Maria Zeb; Muhammad Younas; Hafiz Muhammad Adeel Sharif; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Noor Samad Shah; Xianghui Cao; Afsheen Maryam; Muhammad Qasim (Marine Pollution Bulletin, 2023)

Bioaugmentation and enhanced formation of biogranules for degradation of oil and grease: Start-up, kinetic and mass transfer studies - Maria Nuid; Azmi Aris; Shakila Abdullah; Mohamad Ali Fulazzaky; Khalida Muda (Journal of Environmental Management, 2023)

Addressing women’s climate change awareness in Sindh, Pakistan: an empirical study of rural and urban women - Falak Shad Memon; Fahad Bin Abdullah; Rizwan Iqbal; Sadique Ahmad; Imtiaz Hussain; Maria Abdullah (Climate and Development, 2023)

Synthesis of oxadiazole-thiadiazole fluorochromane hybrids and their antioxidant activity - Mahesh Rupapara; Mehul Chauhan; Chetan B. Sangani; Mohd Afzal; Abdullah Alarifi; Maria Christy; Khushal Kapadiya (Journal of Fluorine Chemistry, 2023)

Knema retusa is antibacterial and antibiofilm against antibiotic resistant Staphylococcus aureus and S. haemolyticus isolated in bovine mastitis - Julalak Chuprom; Kamchai Kidsin; Suthinee Sangkanu; Veeranoot Nissapatorn; Christophe Wiart; Maria de Lourdes Pereira; Tuempong Wongtawan; Mareena Daus; Dennapa Saeloh Sotthibandhu; Varomyalin Tipmanee; Alok K. Paul; Charles Norman Scholfield; et al. (Veterinary Research Communications, 2023)

Assessment of trace elements and fluoride originating from phosphogypsum in the sediment of Gulf of Gabes (southeastern Tunisia): what are the potential sources of accumulation and bioavailability? - Sirine Amri; Lamia Trabelsi; Mohammed Abdullah Dahim; Bochra Brik; Walid Oueslati; Maria Virgínia Alves Martins; Lotfi Aleya; Noureddine Zaaboub (Environmental Science and Pollution Research, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

Experimental transmission of piscine orthoreovirus-1 (PRV-1) in different life stages of Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) - Dhamotharan Kannimuthu; HyeongJin Roh; H Craig Morton; Ma Michelle D. Peñaranda; Anne Vossgård; Tom Hansen; Per Gunnar Fjelldal; Egil Karlsbakk; Ingrid Fiksdal; Maria K. Dahle; Håkon Berg-Rolness; Stig Mæhle; et al. (Frontiers in Marine Science, 2023)
Piscine orthoreovirus -1 (PRV-1) causes the disease heart and skeletal muscle inflammation (HSMI) in farmed Atlantic salmon, and the virus has been detected in wild anadromous Atlantic salmon and brown trout. However, the infection prevalence, viral kinetics, and disease severity in different life stages of Atlantic salmon and brown trout are unknown. The current study aimed to evaluate and compare susceptibility to PRV-1 infection and development of HSMI in different life stages of anadromous Atlantic salmon ( Salmo salar ) and brown trout ( Salmo trutta ). We challenged Atlantic salmon and brown trout fry, parr, and post-smolts with PRV-1 by bath, cohabitation, or IP injection. The kinetics of viral infection and disease development were evaluated by RT-qPCR, in situ hybridization, and histology. Our results indicated that PRV-1 infection prevalence and viral kinetics depend on the developmental stage and challenge method in both Atlantic salmon and brown trout. All developmental stages of Atlantic salmon and brown trout can be infected with PRV-1. However, brown trout showed a lower infection prevalence, with positive cases exhibiting only mild infections without any pathological changes in the target organs, while all life stages of Atlantic salmon developed heart lesions characteristic of HSMI. These results strongly suggest that brown trout are less susceptible to PRV-1 infection than Atlantic salmon and further confirm the species-specific susceptibility and disease development for PRV-1 infection.

8-Hydroxyquinoline a natural chelating agent from Streptomyces spp. inhibits A549 lung cancer cell lines via BCL2/STAT3 regulating pathways - Joseph Devadass Balthazar; Maria Packiam Soosaimanickam; C. Emmanuel; Thirugnansambantham Krishnaraj; Abdullah Sheikh; Saleh Fahad Alghafis; Hairul-Islam Mohamed Ibrahim (World Journal of Microbiology and Biotechnology, 2022)

Traceological analysis of lithics from the Camel Site, al-Jawf, Saudi Arabia: an experimental approach to identifying mineral processing activities using silcrete tools - Yamandú H. Hilbert; Ignacio Clemente-Conte; Rémy Crassard; Guillaume Charloux; Maria Guagnin; Abdullah M. AlSharekh (Archaeological and Anthropological Sciences, 2022)
The Camel Site is in the north of Saudi Arabia in the province of al-Jawf. It is characterised by three decaying sandstone hillocks with life-sized 3D engravings (or reliefs) of camels and equids likely carved during later prehistory. A survey in the central area of the site identified clusters of flakes and other flintknapping remains in the lower areas between the sandstone spurs and larger silcrete tools directly underneath the animal depictions. Some of these tools presented abraded edges, possibly from prolonged contact with the soft and abrasive sandstone that constitutes the rock spurs where the animals were carved. Experiments were performed to test this hypothesis and have a reference collection for further traceological analysis. The chaine opératoire of the experimental engraving tools, from raw material procurement, tool manufacture and use, reuse and discard, was conducted with locally available materials comparable to the archaeological specimens. Specific experimental variables, including how the force was applied, in what direction the movement took place and the orientation of the stone tool during the experiment, were also recorded. Macro- and microscopic analyses of the experimental collection and a sample of archaeological artefacts seem to show that the ancient tools found on the surface were probably used to make the camelid and equid reliefs at the site.

After the smoke has cleared: Extended low fruit productivity following forest fires decreased gregariousness and social tolerance among wild female Bornean orangutans (Pongo pygmaeus wurmbii) - Alison M. Ashbury; Jade Meric de Bellefon; Julia A. Kunz; Misdi Abdullah; Anna M. Marzec; Caroline Fryns; Sri Suci Utami Atmoko; Carel P. van Schaik; Maria A. van Noordwijk (International Journal of Primatology, 2022)
As climate change continues to fundamentally alter resource landscapes, the ability to flexibly respond to spatio-temporal changes in the distribution of preferred food sources is increasingly important for the overall health and fitness of animals living in seasonal, variable, and/or changing environments. Here, we investigate the effects of an uncharacteristically long period of fruit scarcity, following widespread thick haze caused by peat and forest fires in 2015, on the behaviour and sociality of female Bornean orangutans ( Pongo pygmaeus wurmbii ). We collected data from 2010 to 2018 at Tuanan, Central Kalimantan, Indonesia, and compared the activity, diet, and association patterns of adult females during low-fruit periods before the fires, i.e., regular, seasonal periods of low fruit availability (“pre-fire”), and after the fires, i.e., during the extended period of low fruit availability (“post-fire”). First, we found that, post-fire, female orangutans adopted a more extreme energy-saving activity pattern and diet — resting more, travelling less, and diet-switching to less-preferred foods — compared to pre-fire. Second, we found that the probabilities of association between females and their weaned immature offspring, and between related and unrelated adult females were lower, and the probability of agonism between unrelated females was higher, post-fire than pre-fire. This change in energetic strategy, and the general reduction in gregariousness and social tolerance, demonstrates how forest fires can have lasting consequences for orangutans. Fission–fusion species such as orangutans can mitigate the effects of changes in resource landscapes by altering their (sub)grouping patterns; however, this may have long-term indirect consequences on their fitness.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Synthesis, Structure Study, First-Principles Investigations and Luminescence Properties of Europium and Terbium Complexes - Bakhat Ali; Helio A. Stefani; Muhammad Imran; Ahmad Irfan; Mohammed A. Assiri; Maria Claudia F. C. Felinto; Muhammad Khalid; Abdullah G. Al-Sehemi (Journal of Fluorescence, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Two new species of the Fusarium solani species complex isolated from compost and hibiscus (Hibiscus sp.) - Adnan Šišić; Abdullah M. S. Al-Hatmi; Jelena Baćanović-Šišić; Sarah A. Ahmed; Dominic Dennenmoser; G. Sybren de Hoog; Maria R. Finckh (Antonie van Leeuwenhoek, 2018)

Rock art provides new evidence on the biogeography of kudu ( Tragelaphus imberbis ), wild dromedary, aurochs ( Bos primigenius ) and African wild ass ( Equus africanus ) in the early and middle Holocene of north‐western Arabia - Maria Guagnin; Ceri Shipton; Sarah el‐Dossary; Moudhy al‐Rashid; Farès Moussa; Mathew Stewart; Florian Ott; Abdullah Alsharekh; Michael D. Petraglia (Journal of Biogeography, 2018)
Aim Our knowledge of the prehistoric distribution of animal species is so far largely dependent on the location of excavated archaeological and palaeontological sites. In the absence of excavated faunal remains, many species that were present in the Levant and North Africa have been assumed to have been absent on the Arabian Peninsula. Here, we explore representations of four species that were identifiable in the rock art, but had not previously been reported in north‐western Arabia. Location Jubbah and Shuwaymis UNESCO world heritage rock art sites in Ha'il province, north‐western Saudi Arabia. Methods In total, the rock art panels surveyed and recorded in Jubbah and Shuwaymis contain 6,618 individual animal depictions. Species were identified based on diagnostic features of the anatomy. The resulting dataset was then compared to the faunal spectrum reported in the (archaeo)zoological literature. Results The rock art dataset provides evidence that the distributions of lesser kudu ( Tragelaphus imberbis ), wild camel and African wild ass ( Equus africanus ) extended into the north‐west of Arabia and that the engravers may have had knowledge of aurochs ( Bos primigenius ). Main conclusions The presence of previously undocumented mammal species in Arabia provides new information regarding their distribution, as well as the types of habitat and vegetation that were available in prehistoric landscapes. Moreover, the presence of kudu on the Arabian Peninsula indicates that the identification of palaeo‐distributions based exclusively on faunal remains may miss key species in the Afro‐Eurasian faunal exchange.

Efficient genetic transformation and regeneration system from hairy root of Origanum vulgare - Peyman Habibi; Maria Fatima Grossi de Sa; André Luís Lopes da Silva; Abdullah Makhzoum; Jefferson da Luz Costa; Ivo Albertto Borghetti; Carlos Ricardo Soccol (Physiology and Molecular Biology of Plants, 2016)

Novel sequence variants in the TMIE gene in families with autosomal recessive nonsyndromic hearing impairment - Regie Lyn P. Santos; Hatem El-Shanti; Shaheen Sikandar; Kwanghyuk Lee; Attya Bhatti; Kai Yan; Maria H. Chahrour; Nathan McArthur; Thanh L. Pham; Amjad Abdullah Mahasneh; Wasim Ahmad; Suzanne M. Leal (Journal of Molecular Medicine, 2006)